Impact of Smoking Cessation on Periodontal Tissues - Poliana Mendes Duarte; Cristiana Fernandes Plutarco Nogueira; Sarah Monique Silva; Cláudio Mendes Pannuti; Karin C. Schey; Tamires Szeremeske Miranda (Elsevier, 2022)
There is cumulative evidence supporting the negative effects of smoking on periodontal tissues. Smoking cessation can be successfully accomplished through specific programs, including behaviour modification and medications, and has been suggested as a suitable way to reduce the risk of several diseases, including periodontitis. The aim of this review is to provide a concise overview of the current knowledge about the impact of smoking cessation on periodontal tissues and therapy, with data from studies published in the last 15 years. Literature was searched using Medline database from 2005 up to and including September 2020 using medical subject heading (MeSH) terms and other search terms, restricted to the English language. Studies were evaluated and summarised in a narrative review format. Results demonstrated that there is convincing evidence to support the benefits of tobacco cessation in reducing the risk of periodontitis and tooth loss. In addition, the harmful effects of smoking on periodontal tissues seem to be assuaged as the number of years since quitting increases. The existing current evidence, even limited, also shows that smoking cessation may result in additional benefits to the outcome of nonsurgical periodontal treatment. Periodontal care providers should not only check their patient's smoking habit for estimating risk of disease progression and predictability of periodontal therapy, but they should also help smokers improve their oral and systemic health by providing efficient and personalised tobacco‐cessation counselling and treatment.